The Study of the Effect of Nano -Materials on the Mechanical Properties of Polymer Matrix Composite Materials - Atiyah, Ibrahim (Journal of natural sciences, life and applied sciences, 2019)
In a lot of industrial applications the Composite materials have an essential role. The manufacturing of the new composite materials is intended improve the materials applicability. In this work, the influence of silica Nano filler type-and compared that effect with that of silica micro fillers-on mechanical properties of polyester have been investigated. For this purpose, mechanical testing have been used. The addition of Nano silica and micro silica was in different percentages 1%, 3%, and 5%, due to the fact that Polyester is one of matrix of polymer that is frequently used with strengthening fibers for sophisticated applications of composites because of its resistance to corrosion, cost that is low, smooth coping, and its ability to prevent the outbreak of flame.